If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -18 = 10 + x Reorder the terms: -18 + 3x = 10 + x Solving -18 + 3x = 10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -18 + 3x + -1x = 10 + x + -1x Combine like terms: 3x + -1x = 2x -18 + 2x = 10 + x + -1x Combine like terms: x + -1x = 0 -18 + 2x = 10 + 0 -18 + 2x = 10 Add '18' to each side of the equation. -18 + 18 + 2x = 10 + 18 Combine like terms: -18 + 18 = 0 0 + 2x = 10 + 18 2x = 10 + 18 Combine like terms: 10 + 18 = 28 2x = 28 Divide each side by '2'. x = 14 Simplifying x = 14
| -11z=154 | | ln(x)=0.85 | | 5x+10=4x-1 | | 21+z=35 | | 7m=9(n+4) | | 10(4u+3v)+7(3u+3v)= | | x/2.4=4 | | 20-12h= | | 4x^3-3x-0.5=0 | | 21y+1= | | 7x^5-.33x^5=0 | | (4+6)x(17-7)= | | 2y^2-8y=0 | | 3y^2+12y-420=0 | | 40x=10y+8 | | X^5-8x^4=0 | | 40x+10y=8 | | 8(b-5)= | | 3x^2+14x-1=12x | | 3e^1-x=15 | | -10+8x=6x-4 | | 4k-2=4(k-2) | | 5x-2(x+3)=30 | | 11x-4(x+2)=2x+4 | | lnx+ln(x+2)=ln(x-12) | | u(v+6)+w(v-3)=z(v-1) | | 11x-(X+2)=2x+4 | | w+1/8w-6/5=1/4(w-3/5) | | 3x^2+110=4x^2+1x | | 4y=27-10 | | v+5/8v-1/4=4/5(v-7/8) | | -(5w-x)+6(-6x+2w)= |